Implementing solutions to barriers to on-site HIV testing in substance abuse treatment: A tale of three facilities. (April 2015) - Hood, Kristina B.; Robertson, Angela A.; Baird-Thomas, Connie
Highlights: We sought to integrate on-site rapid HIV testing in three drug treatment facilities in the Mississippi Delta. Offer and acceptance rates increased in two centers after barriers were addressed. Rates remained high for a third center that previously offered opt out HIV testing. Addressing implementation barriers is vital for integrating on-site testing into treatment. Abstract: Due to the scarcity of resources for implementing rapid onsite HIV testing, many substance abuse treatment programs do not offer these services. This study sought to determine whether addressing previously identified implementation barriers to integrating on-site rapid HIV testing into the treatment admissions process would increase offer and acceptance rates. Results indicate that it is feasible to integrate rapid HIV testing into existing treatment programs for substance abusers when resources are provided. Addressing barriers such as providing start-up costs for HIV testing, staff training, addressing staffing needs to reduce competing job responsibilities, and helping treatment staff members overcome their concerns about clients' reactions to positive test results is paramount for the integration and maintenance of such programs.